The Effect of Green Supply Chain Management on Firm Performance Mediated by Green Innovation in Cimahi SMEs, Indonesia - Alia, Syipa; Dwiana Ratnamurni, Elis (Publisher Cv. Inara, 2025)
The accelerated growth of economic activities, large-scale industrial expansion, and technological advancements have intensified competition, including among small and medium enterprises (SMEs). Green supply chain management (GSCM), which integrates environmentally conscious practices into supply chain activities, has become a crucial strategy for balancing industrial growth with environmental preservation. This study examines the impact of GSCM on firm performance, mediated by green innovation, in food and beverage SMEs in Cimahi City, Indonesia. SMEs in this sector significantly contribute to the regional economy while generating substantial waste, underlining the need for sustainable practices. The findings reveal that GSCM positively influences Green Innovation, with a strong effect, but has a weak and insignificant direct impact on firm performance. Green Innovation plays a significant role in improving firm performance, with a positive and significant effect. Additionally, Green Innovation acts as a mediator, partially influencing the relationship between GSCM and firm performance. These results underscore the importance of GSCM and Green Innovation in enhancing firm performance and promoting environmental sustainability in SMEs.